Bagaimana Pandangan Penumpang Terhadap Iklan Komersial di Dalam Penerbangan? - Yudhistira Anugerah Pratama; Husnawati Djabbar (Jurnal Ekonomi Manajemen Perbankan, 2025)
This study aims to explore passengers' perspectives on commercial advertisements presented inside airplane cabins during flights. Using a qualitative phenomenological approach, this research involved in-depth interviews with passengers who had experienced in-flight advertising on both domestic and international routes. Findings indicate that passengers are more receptive to advertisements that are contextually relevant, such as promotions for destinations, local services, or travel tips. Psychological factors like mood, fatigue, and emotional needs influence perceptions, with narrative and calming visuals being perceived as more effective. Additionally, cultural background significantly shapes responses to advertising, passengers from collectivist cultures prefer messages that emphasize harmony and togetherness, while those from individualist cultures favor direct and personal messages. These results highlight importance of designing in-flight advertising strategies that are contextually appropriate, personally engaging, and culturally sensitive, especially within the limited space of an aircraft cabin.